The AREST CF experience in biobanking — More than just tissues, tubes and time - Garratt, L.; Kicic, Anthony; Robertson, C.; Ranganathan, S.; Sly, P.; Stick, S. (Elsevier, 2017)
© 2017 European Cystic Fibrosis Society Research to further improve outcomes for people with CF is dependent upon well characterised, archived and accessible clinical specimens. The recent article by Beekman et al. published in Journal of Cystic Fibrosis summarised a scientific meeting at the 13th ECFS Basic Science Conference. This meeting discussed how well-annotated, clinical biobanks for CF could be established in Europe to meet the needs of therapeutic development. The Australian Respiratory Early Surveillance Team for Cystic Fibrosis (AREST CF) has conducted biobanking of CF research and clinical specimens since the late 1990s and is custodian of the most comprehensive paediatric CF biobank in the world that focuses on the first years of life. This short communication will describe the approach undertaken by AREST CF in establishing a clinical specimen biobank.